The value of serum C reactive protein in the assessment of severity of HIV infection among children in a resource limited setting - Udoh, Otobong C.; Dixon umo, Ofonime T.; Bassey, Enobong U. (International Journal of Research in Medical Sciences, 2020)
Background: Human immuno-deficiency virus (HIV) infection has devastating impact especially on well-being of children. Management of HIV infected children in resource-limited countries poses significant difficulties. The role of C-reactive protein as a potentially useful/cost-effective tool for assessing severity of HIV infection is yet to be established. The relationship between serum C-reactive protein and severity of HIV infection among children aged 6 months to 12 years was evaluated. Methods: Authors recruited 85 children each on combined antiretrovirals for ≥3 months, and apparently healthy HIV-negative controls. Severity of HIV infection was assessed by classification into immunologic categories 1, 2, 3 and clinical categories N, A, B, C according to the Centre for Disease Control revised classification system. Enzyme linked immunosorbent assay (ELISA) was used for serum CRP estimation. CD4 count was estimated by flow cytometry. Data analysis was with Statistical Package for Social Sciences version 20. Results: Response rate was 160 (94.1%) with mean age of participants being 8.50±3.36 years. Male to female ratio was 1.35:1. Lymphadenopathy was the commonest clinical feature in 26 (32.50%) participants, 59 (73.75%) participants were asymptomatic, and 52 (65.00%) were immunologic stage 1. Median serum CRP of HIV infected group and controls were 4.2 (1-13.9) mg/l and 0.5 (0.2-1.9) mg/l respectively. There was an association between Clinical and immunolological stages of infection and levels of serum CRP, p values = 0.001 and 0.002 respectively. Conclusions: The serum level of CRP may predict the severity of HIV infection among children.